Microsatellite Polymorphisms Adjacent to the Oxytocin Receptor Gene in Domestic Cats: Association with Personality? - Arahori, Minori; Chijiiwa, Hitomi; Takagi, Saho; Bucher, Benoit; Abe, Hideaki; Inoue-Murayama, Miho; Fujita, Kazuo (Frontiers in Psychology, 2017)
A growing number of studies have explored the oxytocin system in humans and non-human animals, and some have found important genetic polymorphisms in the oxytocin receptor gene (OXTR) associated with the bonding system, social behaviors, and personality in several species. Although single nucleotide polymorphisms in OXTR have been well examined in various species, microsatellites (or short tandem repeats) adjacent to OXTR have rarely been studied, despite some suggestions that microsatellite polymorphisms near genes might play a role in genetic transcription and translation. In this study, we surveyed microsatellites in the upstream, intron and downstream regions of OXTR in domestic cats (Felis catus). We succeeded in amplifying 5 out of 10 regions, and recognized these 5 regions as polymorphic. We compared allele frequencies in these 5 regions between mongrel cats in Japan (n = 100) and cats of 10 pure breeds (n = 40). There were significant differences in allele frequencies between the two populations in all microsatellite regions. Additionally, the owners of mongrel cats answered a comprehensive personality questionnaire, and factor analysis extracted four factors (Openness, Friendliness, Roughness, and Neuroticism). We examined the association between the microsatellite genotypes, age, sex, neutering status, and personality scores. Compared to their counterparts, younger cats tended to score higher on Openness, male cats scored higher on Friendliness, and female and neutered cats scored higher on Roughness. When we divided the sample into three groups depending on the length of alleles, we found a marginally significant association between Friendliness and MS3. Additionally, we found a sex-mediated effect of genotypes in MS4 on Friendliness, resulting in different effects on females and males. Our findings that mongrel cats had longer alleles in MS3 and MS4 than purebred cats, and that those cats tended to score higher on Friendliness, supported the previous findings. However, future studies such as comparison between purebred cats with apparently different origin or personality are required to determine the association of genetic variants in the OXTR with personality.